2007
DOI: 10.1111/j.1479-828x.2007.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of intrapartum fetal surveillance education practices in Victorian public hospitals

Abstract: These data reveal important deficiencies in the provision and quality of current IFS education practices in Victoria, particularly in smaller and rural hospitals. However, these deficiencies seem to reflect a lack of opportunity rather than a lack of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…This was consistent with reports from Canada and the United States 4–6 and a 2004 survey undertaken in Victoria by Beaves et al. 7 In 2005, Beaves and colleagues have subsequently reported significant intrapartum fetal surveillance deficiencies in 10 hospitals surveyed within Victoria 8…”
Section: Introductionsupporting
confidence: 83%
“…This was consistent with reports from Canada and the United States 4–6 and a 2004 survey undertaken in Victoria by Beaves et al. 7 In 2005, Beaves and colleagues have subsequently reported significant intrapartum fetal surveillance deficiencies in 10 hospitals surveyed within Victoria 8…”
Section: Introductionsupporting
confidence: 83%
“…What remains to be seen is whether the perceived educational value translates into sustained longer term educational benefits to the work force and, ultimately, to a reduction in the perinatal mortality and morbidity associated with poor IFS practice. In contrast to before 2004, 7 at least clinicians in Australia and New Zealand now have access to a high quality education product, irrespective of who they are or where they practice.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, deficient care has been identified in as many as 75% of cases of intrapartum‐related stillbirths and neonatal deaths, 5,6 leading to a call for regular training in IFS for all clinicians involved in the care of labouring women 1 . However, a recent survey of Victorian public hospitals revealed a distinct lack of provision of quality IFS education, 7 particularly in smaller and regional hospitals. Recognising the urgent need for effective education, the Royal Australian and New Zealand College of Obstetrics and Gynaecology (RANZCOG) developed and introduced the Fetal Surveillance Education Program (FSEP) with funding from the Victorian Government's Department of Human Services and the Victorian Managed Insurance Authority.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of these national reports and the UK recommendations, it is perhaps surprising that options for formal education and credentialing in fetal surveillance remain limited. A recent survey of education and credentialing practices at public maternity hospitals in Victoria reported that only 33% had an existing intrapartum fetal surveillance education program in place and only 10% had some form of credentialing [ 5 ].…”
Section: Introductionmentioning
confidence: 99%